Designing user innovation toolkits: exploring the interrelation between solution space and module library. Issue 3 (1st October 2016) - Helminen, Pia; Ainoa, Juha; Mäkinen, Samuli
Abstract : The importance of involving users in the development of products and services is widely noted. Utilizing physical models and representations collaboratively as a means for transferring the "sticky" knowledge from user to developer is a direction many have chosen. Many of these methods, such as design games, probes, and tangible business modeling, share common elements, but the interrelations of these elements are not well understood. The aim of this paper was to explore the interrelation of the module library and the solution space by using a user innovation toolkit in the context of shopping center design. Three different versions of a user innovation toolkit, where the solution space and the content of the module library vary, are created in the form of a "puzzle" containing physical building blocks. This preliminary exploration suggests that in order to ensure that users communicate their own individual needs, both the solution space and the module library should be opened up. Looking into the relationship of the module library and the solution space benefits not only the development of user innovation toolkits but also other methods and techniques commonly used by designers.